Design and development of optimum modular carbon capture adsorption bed - Luqman Hisham Bin Hisamuddin (2023)
In this thesis consists of designing an optimum modular carbon capture embedded for power plant mainly used for Tenaga Nasional Berhad Company. The design consists of primary modular design and secondary modular design. The significant differences between both of it is the primary module are better approach as the performance and efficiency are in good shape between secondary modular design. The focused techniques in this thesis are using pressure swing adsorption. In this thesis contains the study of simulation of the modular design in using the dual set Langmuir theorem and Dubinin-Astakahov approach for finding CO2 adsorption isotherm. The properties of Metal Organic Framework (Mg-MOF-74) and Activated Carbon are provided in this thesis. The simulation of the modular in other aspects contains the mesh independence analysis to improvise numerical data in mesh generation for Computational Fluid Dynamics (CFD) software mainly in Ansys Fluent and by the results also providing CO2 concentration contour[1].